2019
DOI: 10.1055/a-0974-3991
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the GREAT Score in Turkish Patients with Gravesʼ Hyperthyroidism Treated with the Titration Regimen Method of Antithyroid Drugs: A Multicenter Study

Abstract: Recently, the Gravesʼ Recurrent Events After Therapy score (GREAT) was proposed as a useful tool to predict relapse before starting antithyroid drugs (ATD) in patients with Gravesʼ disease (GD). Therefore, we intended to assess the validity of the GREAT score in Turkish patients with GD, including patients who experienced a poorly controlled disease (multiple episodes of hyperthyroidism followed by euthyroidism or rarely hypothyroidism) during ATD dose titration. This is a retrospective multicenter study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…However, although TRAb levels were significantly higher in younger male patients, in regression analysis, age at diagnosis was not found to be an independent contributor to TRAb levels. We believe that higher TRAb levels observed in male patients at the initial diagnosis of GD in our study could support the results of prior studies reporting a higher frequency of relapse after discontinuation of the antithyroid drugs as well as a more severe disease course in male patients with GD [11,12,20].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, although TRAb levels were significantly higher in younger male patients, in regression analysis, age at diagnosis was not found to be an independent contributor to TRAb levels. We believe that higher TRAb levels observed in male patients at the initial diagnosis of GD in our study could support the results of prior studies reporting a higher frequency of relapse after discontinuation of the antithyroid drugs as well as a more severe disease course in male patients with GD [11,12,20].…”
Section: Discussionsupporting
confidence: 90%
“…The age of the patient during the first diagnosis is another factor associated with the outcome of GD. Patients < 40 years old at diagnosis have also a higher risk of relapse after treatment with ATDs [12,13]. However, the association between gender as well as age with TRAb at the initial diagnosis of GD is not well known.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it is demonstrated that patients with goiter gradation Grade II and above have a higher recurrence rate and relapse in a relatively short period of time than patients with goiter gradation Grade I. This finding is in agreement with that of Turkish study enrolled 517 patients with GD after ATD withdrawal ( 30 ). Meanwhile, there has also been an association between goiter and relapse after ATD withdrawal in previous studies ( 28 , 31 ).…”
Section: Discussionsupporting
confidence: 88%
“…The relapse rates in class I, II, and III of this so-called Graves' recurrent events after therapy (GREAT) score were 16%, 44%, and 68%, respectively. The GREAT scoring system has been validated in three studies (35)(36)(37). Table 2 shows the results of GREAT risk scores in four studies.…”
Section: Overall Costmentioning
confidence: 99%